System Geographical Webbing as an Object of Knowing to Analyze Sustainability Issues in Geography - Dessen Jankell, Lotta; Johansson, Patrik (Journal of Geography Education, 2023)
This article explores system geographical webbing, i.e., to use a specific connection web to analyze sustainability issues, as an object of knowing in upper secondary Geography teaching. A model task was developed based on systems principles and geographical concepts. Empirical data consists of teaching interventions aimed at encouraging students to perform webbing actions and to construct geographical relationships of sustainability issues. The article describes aspects of the geographical knowing needed for using a connection web and its embedded tools to explore sustainability issues. Finally, the article suggests avenues for teachers to support system geographical knowing development.
Keywords: Geography teaching, systems thinking, system geographical webbing, sustainability issues